Characteristic curves of hydrogenated amorphous silicon based solar cells modeled with the defect pool model - Klimovsky, E. (2007)
Using the improved expression of the defect pool model proposed by Powell and Deane we match the experimental current–voltage and the spectral response characteristic curves of hydrogenated amorphous silicon solar cells. We compare the electrical parameters resulting from using the different defect pool models published in the literature and from assuming a uniform density of dangling bond in every device layer. We discuss the applicability of the algorithm derived by Schumm for the stabilized state exploring its sensitivity to the sample history. Finally we propose an expression for stabilized cells adapting Schumm's ideas to the expression derived by Powell and Deane.